Net-Zero Emissions Pathways in BRICS Economies: The Impact of Environmental Innovations, Policy, and Human Capital on Carbon Footprint Reduction - Alkofahi, Kolthoom; Duran, Ivan A.; Saqib, Najia (International Journal of Energy Economics and Policy, 2024)
The present study investigates the interconnection between environmental technology and policy frameworks in the context of pollution mitigation, focusing specifically on the BRICS economies since 1994 until 2021. Their detrimental impacts and the congruence of remedial measures with Sustainable Development Goals (SDGs) emphasize the need of addressing global environmental contaminants promptly. In addition, the very ambitious decarbonization goals of the Paris Accord have generated discussions concerning the sufficiency of existing environmental policies in stimulating essential technical advancements by 2030. By utilizing sophisticated econometric techniques such as CS-ARDL and AMG, this work offers reliable long-term estimations. Findings demonstrate that environmentally friendly technology are highly effective in reducing pollution levels. Additional evidence indicates that strict environmental regulations, together with the use of renewable energy and the improvement of human skills through education, are crucial for decreasing carbon footprint. In conclusion, the study provides policy suggestions to enhance these endeavours, therefore making a valuable contribution to wider environmental sustainability objectives.